PENATALAKSANAAN FISIOTERAPI DENGAN MODALITAS TENS, MYOFASCIAL RELEASE, STRENGTHENING EXERCISE, DAN CERVICAL TRACTION PADA KASUS CERVICAL ROOT SYNDROME - Khairunnisa, Fatimah As-Syifa; Wijianto, Wijianto (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Cervical root syndrome is a condition of cervical nerve root compression. This nerve root compression causes some symptoms such as pain, cervical muscle spasm, cervical range of motion limitations, and decrease of muscle strength which lead to activity dailiy life limitation. This study applies TENS, myofascial release, cervical traction, and strengthening exercise as physiotherapy interventions. The aim of this study is to find out the effect of TENS, myofascial release, cervical traction, and strengthening exercise as physiotherapy management on patient with cervical root syndrome. This is a case report study conducted on a patient with cervical root syndrome in RSUP Dr. Sardjito Yogyakarta in November to December 2024. This study uses several measurement for each instrument, those are Numeric Rating Scale (NRS) for pain, goniometer for Range of Motion (ROM), Manual Muscle Test (MMT) for muscle power, and Neck Disability Index (NDI) for activity daily life. The result of this study is the physiotherapy management of TENS, myofascial release, cervical traction, and strengthening exercise affects in decreasing pain, increasing range of motion, muscle power, and activity daily life on patient with cervical root syndrome.